Isoprenoids and phenylpropanoids are part of the antioxidant defense orchestrated daily by drought‐stressed Platanus × acerifolia plants during Mediterranean summers. Issue 3 (17th March 2015) - Tattini, Massimiliano; Loreto, Francesco; Fini, Alessio; Guidi, Lucia; Brunetti, Cecilia; Velikova, Violeta; Gori, Antonella; Ferrini, Francesco
Summary: The hypothesis was tested that isoprenoids and phenylpropanoids play a prominent role in countering photooxidative stress, following the depletion of antioxidant enzyme activity in plants exposed to severe drought stress under high solar irradiance and high temperatures. Platanus × acerifolia, a high isoprene‐emitting species, was drought‐stressed during summer (WS) and compared with unstressed controls (WW). Water relations and photosynthetic parameters were measured under mild, moderate, and severe drought stress conditions. Volatile and nonvolatile isoprenoids, antioxidant enzymes, and phenylpropanoids were measured with the same time course, but in four different periods of the day. Drought severely inhibited photosynthesis, whereas it did not markedly affect the photochemical machinery. Isoprene emission and zeaxanthin concentration were higher in WS than in WW leaves, particularly at mild and moderate stresses, and during the hottest hours of the day. The activities of catalase and ascorbate peroxidase steeply declined during the day, while the activity of guaiacol peroxidase and the concentration of quercetin increased during the day, peaking in the hottest hours in both WW and WS plants. Our experiment reveals a sequence of antioxidants that were used daily by plants to orchestrate defense against oxidative stress induced by drought and associated high light and high temperature. Secondary metabolites seem valuable complements of antioxidant enzymes to counter oxidative stress during the hottest daily hours.